Ориентация амфибий при выключенных некоторых органах чувств - Лялюшко, Д.M.; Пащенко, Ю.С.; Бабенко, Л.А. (Вестник зоологии, 1972)
Orientation was studied of Rana terrestris A n d r z e j e w s k i for a water body in the period of reproduction from a distance of 150 m, olfactory, sight and auditory organs being eliminated. It was established that elimination of sight and auditory organs causes no disturbance in orientation whereas elimination of olfactory organs evokes a complete desorientation.